Analysis of the Sugarcane Biomass Use to Produce Green Hydrogen: Brazilian Case Study - Gustavo Henrique Romeu da Silva; Andreas Nascimento; Diego Nascimento; Julian David Hunt; Mauro Hugo Mathias (Applied Sciences)
Conventional hydrogen production processes, which often involve fossil raw materials, emit significant amounts of carbon dioxide into the atmosphere. This study critically evaluates the feasibility of using sugarcane biomass as an energy source to produce green hydrogen. In the 2023/2024 harvest, Brazil, the world’s largest sugarcane producer, processed approximately 713.2 million metric tons of sugarcane. This yielded 45.68 million metric tons of sugar and 29.69 billion liters of first-generation ethanol, equivalent to approximately 0.0416 liters of ethanol per kilogram of sugarcane. A systematic literature review was conducted using Scopus and Clarivate Analytics Web of Science, resulting in the assessment of 335 articles. The study has identified seven potential biohydrogen production methods, including two direct approaches from second-generation ethanol and five from integrated bioenergy systems. Experimental data indicate that second-generation ethanol can yield 594 MJ per metric ton of biomass, with additional energy recovery from lignin combustion (1705 MJ per metric ton). Moreover, advances in electrocatalytic reforming and plasma-driven hydrogen production have demonstrated high conversion efficiencies, addressing key technical barriers. The results highlight Brazil’s strategic potential to integrate biohydrogen production within its existing bioenergy infrastructure. By leveraging sugarcane biomass for green hydrogen, the country can contribute significantly to the global transition to sustainable energy while enhancing its energy security.